Vegetative Propagation through Juvenile Shoot Cuttings of Melia composita Willd. - Luna, R. K.; Kumar, Suresh (Indian Forester, 2006)
Melia composita is a fast growing tree species popularly grown in homesteads and agroforestry plantations. Effects of 1000, 2000 and 3000 ppm of IBA, IAA and NAA were studied on the rooting ability, sprouting percentage, sprout length, number of leaves, number of roots and length of roots in juvenile shoot cuttings of Melia composita from March 2005 to September 2005 under intermittent mist conditions. IBA 3000 ppm produced the best results giving 57.14% rooting, 3.92 roots per rooted cutting and 4.31 cm mean root length in 45-50 days. Among the months, July planted cuttings gave the best results. The technology can be used to multiply superior genotypes for tree improvement and mass propagation for afforestation programmes.